2019
DOI: 10.3390/ijns5030029
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Carnitine Deficiency in Extremely Preterm Neonates Related to Parenteral Nutrition: Two Step Newborn Screening Approach

Abstract: Currently, there is no evidence in the literature to support the routine supplementation of all parenterally fed premature infants with l-carnitine. In our study, we found that about 8.56% of extremely preterm neonates are diagnosed with carnitine deficiency secondary to malnutrition, either due to reduced stores at birth or related to total parenteral nutrition (TPN). Our two step approach of performing newborn screening (NBS) again at 32 weeks gestational age (GA) equivalent helps to diagnose 81.4% more pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…RDS in neonates, is still a primary etiology of morbimortality in preterm infants and it is considered one of the main etiology of NICU admission [8] . Carnitine plays an essential role in β oxidation as it transports long chain fatty acids across the mitochondrial membrane [9] . Reduction in neonatal serum carnitine levels in preterm infants with RDS throughout the first week of life, which may be due to the increasing consumption of carnitine in lung tissue for surfactant synthesis and may be owing to low levels of α-butyrobetaine hydroxylase, a catalyzing enzyme in the last step of the carnitine biosynthesis [7] .…”
Section: Discussionmentioning
confidence: 99%
“…RDS in neonates, is still a primary etiology of morbimortality in preterm infants and it is considered one of the main etiology of NICU admission [8] . Carnitine plays an essential role in β oxidation as it transports long chain fatty acids across the mitochondrial membrane [9] . Reduction in neonatal serum carnitine levels in preterm infants with RDS throughout the first week of life, which may be due to the increasing consumption of carnitine in lung tissue for surfactant synthesis and may be owing to low levels of α-butyrobetaine hydroxylase, a catalyzing enzyme in the last step of the carnitine biosynthesis [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Efforts have allowed NBS programs to emerge, resulting from pilot programs and successful studies [ 45 , 46 , 47 ]. However, to date, only Qatar and Saudi Arabia have included PCD in their programs [ 48 , 49 , 50 ].…”
Section: Worldwide Overview Of Primary Carnitine Deficiency Newborn S...mentioning
confidence: 99%
“…135 Preterm infants are at risk for relative deficiency of carnitine because of their dependence on lipids as an energy source and limited endogenous synthetic ability, although the clinical need is still unproven. 136 Carnitine is detectable in HM and is currently added to standard term and preterm formulas. 137 In preterm infants not receiving supplemental carnitine, plasma and tissue carnitine levels may fall even in the presence of adequate precursor amino acid concentrations.…”
Section: Long-chain Polyunsaturated Fas In Hmmentioning
confidence: 99%
“…137 In preterm infants not receiving supplemental carnitine, plasma and tissue carnitine levels may fall even in the presence of adequate precursor amino acid concentrations. 136,138 Yaron et al 139 showed that infants fed with a formula supplemented with β-16:0 for 6 weeks showed more Lactobacillus and Bifidobacterium genera in their stools than a control group that received formula containing vegetable-sourced 16:0. The mechanisms are unclear, but there is a possibility that the position of palmitic acid on the TAGs may have influenced that gut microbiome.…”
Section: Long-chain Polyunsaturated Fas In Hmmentioning
confidence: 99%